Enhancing anaerobic biodegradability and dewaterability of sewage sludge by microwave irradiation - Fang, Gao; Zhou, Xia; Wei, Wang (International Journal of Agricultural and Biological Engineering, 2017)
Thermal hydrolysis was an effective pretreatment for the sewage sludge by improving dewatering and anaerobic digestion but the heating was a time-consuming process. This study focused on the effects of the microwave irradiation by using high temperature and pressured system on sewage sludge hydrolysis. The results obtained in current research showed that sludge could absorb microwave energy with high efficiency and then be hydrolyzed fast. The solubilization of suspended solid (SS), volatile suspended solids (VSS) and the increasing of the level of soluble chemical oxygen demand (SCOD) in liquid fraction showed that the microwave irradiation could be shortened to 5 min under a temperature range of 80°C-170°C. The highest value of VSS dissolution ratio (36.4%) was obtained at 170°C for 30 min. The COD dissolution ratio was about 25% at 170°C. The improvement of the biogas production from both mixture sludge and waste activated sludge was 20.2% and 25.9% respectively at 170°C for 10 min. The dewaterability of sludge was greatly improved. Subsequently, the sludge volume could be reduced by 60% with microwave irradiation. Keywords: sludge, microwave irradiation, biogas production, dewaterability DOI: 10.3965/j.ijabe.20171002.2871 Citation: Gao F, Xia Z, Wang W. Enhancing anaerobic biodegradability and dewaterability of sewage sludge by microwave irradiation. Int J Agric & Biol Eng, 2017; 10(2): 224–232.